Analisis Yuridis Pemberhentian Hakim Mahkamah Konstitusi oleh Dewan Perwakilan Rakyat Republik Indonesia Dihubungkan dengan Undang-Undang Nomor 7 Tahun 2020 Tentang Perubahan Ketiga Atas Undang-Undang Nomor 24 Tahun 2003 Tentang Mahkamah Konstitusi - Wahyu Koswara; Deny Guntara; Muhamad Abas; Adyan Lubis (UNES Law Review, 2023)
The reform resulted in changes to the 1945 Constitution, changing the Indonesian constitutional system, including dividing power horizontally functionally, namely the Executive, Legislative and Judiciary Institutions. All three have different powers according to their functions. This is to reinforce the system of checks and balances against the three institutions, but also not to interfere in the affairs of other institutions outside of their powers and functions. The removal of Judge Aswanto is one example of the Legislature's involvement in Judicial affairs, the article being that the removal of Judge Aswanto often annulled laws made by the legislature so that the removal was full of political interests. In this research, it examines and analyzes the dismissal of judges at the constitutional court by the People's Representative Council of the Republic of Indonesia in connection with Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court with a normative juridical research type so that the approach taken is a statute approach, historical approach and conceptual approach. As for the author's view, the decision to remove judge Aswanto from the House of Representatives as a legislative institution shows that the judiciary has lost its value as an independent institution. That the independence of judges should start with transparent appointments and dismissals with due regard to judicial accountability. Furthermore, the judicial power or in this case as an institution of judicial power must be free from any political interests in carrying out its duties and return the concept to Law Number 7 of 2020.